Dopamine receptor antagonists as new mode-of-action insecticide leads for control of Aedes and Culex mosquito vectors. - Andrew B Nuss; Karin F K Ejendal; Trevor B Doyle; Jason M Meyer; Emma G Lang; Val J Watts; Catherine A Hill (Public Library of Science (PLoS), 2015)
BACKGROUND:New mode-of-action insecticides are sought to provide continued control of pesticide resistant arthropod vectors of neglected tropical diseases (NTDs). We previously identified antagonists of the AaDOP2 D1-like dopamine receptor (DAR) from the yellow fever mosquito, Aedes aegypti, with toxicity to Ae. aegypti larvae as leads for novel insecticides. To extend DAR-based insecticide discovery, we evaluated the molecular and pharmacological characteristics of an orthologous DAR target, CqDOP2, from Culex quinquefasciatus, the vector of lymphatic filariasis and West Nile virus. METHODS/RESULTS:CqDOP2 has 94.7% amino acid identity to AaDOP2 and 28.3% identity to the human D1-like DAR, hD1. CqDOP2 and AaDOP2 exhibited similar pharmacological responses to biogenic amines and DAR antagonists in cell-based assays. The antagonists amitriptyline, amperozide, asenapine, chlorpromazine and doxepin were between 35 to 227-fold more selective at inhibiting the response of CqDOP2 and AaDOP2 in comparison to hD1. Antagonists were toxic to both C. quinquefasciatus and Ae. aegypti larvae, with LC50 values ranging from 41 to 208 μM 72 h post-exposure. Orthologous DOP2 receptors identified from the African malaria mosquito, Anopheles gambiae, the sand fly, Phlebotomus papatasi and the tsetse fly, Glossina morsitans, had high sequence similarity to CqDOP2 and AaDOP2. CONCLUSIONS:DAR antagonists represent a putative new insecticide class with activity against C. quinquefasciatus and Ae. aegypti, the two most important mosquito vectors of NTDs. There has been limited change in the sequence and pharmacological properties of the DOP2 DARs of these species since divergence of the tribes Culicini and Aedini. We identified antagonists selective for mosquito versus human DARs and observed a correlation between DAR pharmacology and the in vivo larval toxicity of antagonists. These data demonstrate that sequence similarity can be predictive of target potential. On this basis, we propose expanded insecticide discovery around orthologous DOP2 targets from additional dipteran vectors.